Form and substance: reorienting research in law - Lavado Malqui, Lucas (2022)
The 21st century has started full of changes in many fields of science, technology and humanities. The novelties in the methodological field and above all in the reality that is the scene of it are abuzz. However, in our environment characterized by academic difficulties, it takes time for debates and news to reach the process of research and academic learning contextualized by our complex process as a society. A decisive aspect on this point is the theory of problems and the elucidation of key concepts.